2003
DOI: 10.1099/vir.0.18802-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological characterization of sporadic acute hepatitis E in a Japanese patient infected with a genotype III hepatitis E virus in 1993

Abstract: Serum samples collected periodically from a 40-year-old Japanese woman who had not travelled abroad and who had contracted sporadic acute hepatitis E in 1993 were semi-quantitatively tested by enzyme immunoassay for IgM, IgA and IgG antibodies to hepatitis E virus (HEV). Anti-HEV IgM and IgA antibody levels were the highest (1 : 2400 dilution and 1 : 3400 dilution, respectively) on day 9 after the onset of hepatitis and then decreased rapidly in a parallel manner. Anti-HEV IgG antibody levels were the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…As a consequence, the prevalence of HEV infection could be understimated. IgA type anti-HEV antibody can be utilized as an additional confirmatory antibody for recent HEV infection Tokita et al 2003), and this case demonstrated positive reaction for it in an examination of stocked sera at admission. Also, although judged as negative, the titer of IgM type anti-HEV was weakly reactive on admission and was decreased after time course (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the prevalence of HEV infection could be understimated. IgA type anti-HEV antibody can be utilized as an additional confirmatory antibody for recent HEV infection Tokita et al 2003), and this case demonstrated positive reaction for it in an examination of stocked sera at admission. Also, although judged as negative, the titer of IgM type anti-HEV was weakly reactive on admission and was decreased after time course (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…HEV is a small virus that causes an acute self-limiting infection, even in the face of a robust antiviral immune response (7,42). Previous studies carried out by us and others have shown that the HEV ORF3 protein regulates cellular processes and has three broad roles.…”
Section: Discussionmentioning
confidence: 99%
“…HEV-specific IgA has been detected in sera from acute-HEV patients, and the presence of HEV-specific IgA in combination with IgM was found to be highly specific for the serodiagnosis of acute HEV infections (4,11,16,19,21,22). As the duration of the IgA response seemed limited (19), it was suggested that anti-HEV IgA detection may be useful to discriminate acute and past infections for serological diagnosis of recent (subclinical) HEV infection (15).…”
Section: Hepatitis E Virus (Hev) Infections Are Recognized In Thementioning
confidence: 99%